Lower Triassic Antarctic vertebrate fossils at Field Museum, Chicago, IL - Makovicky, Peter (IEDA: US Antarctic Program Data Center, 2023)
Spreadsheet with provisional taxonomic identification and locality data for Early Triassic vertebrate fossils from the Allen Hills region accessioned at Field Museum, Chicago, IL